Administration of a VEGFR-2-specific MRI contrast agent to assess orthodontic tooth movement A pilot study - Schroeder, Agnes; Seyler, Lisa; Hofmann, Elisabeth; Gölz, Lina; Jantsch, Jonathan; Proff, Peter; Bäuerle, Tobias; Kirschneck, Christian (Journal of Orofacial Orthopedics / Fortschritte der Kieferorthopädie, 2021)
Purpose It is thought that orthodontic forces initially reduce periodontal blood flow during orthodontic tooth movement (OTM) via tissue compression with cells responding to concomitant oxygen deprivation with expression of vascular endothelial growth factor (VEGF) triggering angiogenesis via binding to its receptor VEGFR-2. To test this hypothesis, we performed a pilot study to establish a protocol for molecular magnetic resonance imaging (MRI) of rat jaws administering a VEGFR-2-specific contrast agent. Methods Mesial OTM of a first upper left rat molar was initiated in one male Fischer 344 rat 4 days prior to MRI by insertion of an elastic band between the first and second upper molars with the contralateral side left untreated (internal control). T1-weighted MRI sequences including dynamic contrast-enhanced MRI (DCE-MRI) were recorded before and after administration of a molecular VEGFR-2 MRI marker with a 7 T MRI dedicated for small animal use. Results After injection of anti-VEGFR2-albumin-gadolinium-DTPA, volume enhancement on T1-weighted images was increased at the OTM side distally of the moved first upper molar (M1) compared to the control side, whereas the T1 relaxation time was reduced on the OTM side. DCE-MRI resulted in an increased area under the curve (AUC), whereas time-to-peak (TTP) and washout rate were reduced during OTM distally of the moved M1 compared to the contralateral side. Conclusions OTM resulted in uptake of the VEGFR-2-specific MRI contrast agent in tension areas of the periodontal ligament. The imaging protocol presented here is useful for the assessment of VEGFR-2 expression in tension areas of the periodontal ligament in vivo.
CRIS-Team WoS Importer:2021-07-30